Educación ambiental para el fortalecimiento de las capacidades de los/as estudiantes de la Unidad Educativa Aníbal González Álava, cantón Tosagua - Zambrano Valdez, Hilda Amelia (2020)
The main objective of this research is to evaluate the strengthening of capacities through an environmental education strategy for the students of the Aníbal González Álava Educational Unit, in Ángel Pedro Giler parish in Tosagua canton. The bibliographic, descriptive, deductive and exploratory method was used, techniques such as surveys, observation and training were also used. An initial environmental diagnosis was carried out on 30 students where more than 67% of the respondents have basic knowledge of what environmental education is, but without understanding of carrying out environmental strategies such as recycling, reforestation, ecological nurseries, among others. With the information obtained, the application of a methodological strategy of environmental education for the strengthening of capacities was carried out with four educational workshops, where the students contributed reforestation strategies within their community. The “Learning by Doing” workshop had the highest motivation index, attention and responsiveness in students above 89% satisfaction. During the workshops given, an evaluation of the final environmental knowledge was carried out, where it had a statistical mean of 1.18, that is, there were higher percentages of correct answers, demonstrating that it had a significant difference between the initial and final evaluation (<0, 05) giving rise to the elaboration of a lesson plan on environmental education for the Aníbal Gonzales Álava Educational Unit.